REGIONAL INTEGRATION OPPORTUNITIES IN USING SOLAR AND WIND ENERGY IN CENTRAL ASIA (Universal International Scientific Journal, 2026)
This article provides an in-depth analysis of the state of solar and wind energy potential in Central Asian countries, existing opportunities, and the need for regional integration. The natural resources of the region, the economic and political environment, as well as ways to strengthen regional energy cooperation based on international experience are outlined. The study uses statistical data, SWOT analysis, comparative analysis, and international experience. In conclusion, it is emphasized that regional integration is an important factor in developing the renewable energy market and ensuring sustainable economic growth.
Keywords: Central Asia; solar energy; wind energy